W-Band Hybrid Unequal Feeding Network of Waveguide and Substrate Integrated Waveguide for High Efficiency and Low Sidelobe Level Slot Array Antenna Application - Jun Wang; Yu Jian Cheng (International Journal of Antennas and Propagation)
A W-band hybrid unequal feeding network of waveguide and substrate integrated waveguide (SIW) is presented in this paper. It comprises a two-way hybrid waveguide-SIW E-plane divider and an unequal SIW dividing network. Firstly, the two-way hybrid divider is developed to realize the waveguide-to-SIW vertical transition and power division at the same time. Besides, it has a wider bandwidth and more compact configuration compared with those of conventional structures including a transition and a cascading divider. Secondly, an SIW 1-to-16-way unequal dividing network is developed with the phase self-compensation ability. This W-band dividing network is able to generate the desired amplitude and phase distribution. Finally, two back-to-back SIW 16 × 16 antenna arrays are grouped and fed by the proposed feeding network. The low sidelobe levels (SLLs) can be achieved at E- and H-plane of the antenna. The total aperture size of the antenna is 15% less than that of a conventional antenna with a separated divider and a transition. With such a multifunctional feeding network, the antenna is able to achieve low loss and high efficiency as well.